P6 Factors associated with compliance with nut/seed reintroduction following a negative food challenge – a cohort review from a specialist paediatric allergy unit. (June 2019) - Tarrant, Roslyn; Gregory, Ian; Fitzsimons, Roisin
Abstract : Introduction: Selective nut/seed eating has become standard practice in allergy units across Europe, with studies suggesting there is potential for patients allergic to one nut or seed to incorporate others into their diet. To minimize cross-contamination risk, our unit guidelines provide standards for 'safe selective nut/seed eating' however the compliance rate with such guidelines is unknown. The aim of the current study is to assess patient compliance with nut/seed reintroduction, and examine the factors predictive of full compliance. Methods: Eligible patients who had a negative food challenge to a nut/seed in the preceding 2 and 12 months at a single paediatric allergy unit were identified from an institutional database, and followed up via a telephone interviewer-administered questionnaire in June 2018. Patient compliance with nut/seed reintroduction advice in four domains including frequency of eating (i.e. ≥ 2 times/week), type of food consumed (i.e. whole/ground from single nut/seed pack), age-appropriate portion size, location of eating (i.e. in the home only) was assessed; 'full' compliance denotes compliance with all four domains combined. Data were collected on patient receival of support/information, barriers to compliance, and parental perceptions of the reintroduction experience. Results: From 141 eligible patients, 100 (70.9%) consenting participants were successfully followed up at either 2 (54%) or 12 (46%) months post-challenge; median age was 3.8 years. Only 17% (n = 17) of the sample fully complied with all four domains combined. The highest compliance rate was in the 'location' domain (70%); 39% of patients complied with recommended 'portion size'. The most prevalent reason for not eating the nut/seed as frequently as recommended included 'the child not liking the taste of the food' (n = 24; 41.1%). Fifty five percent (n = 55) of parents reported to receiving hospital literature on nut/seed reintroduction; 15% spoke with a dietitian regarding nut/seed reintroduction advice. Parental agreement with the statement 'my child likes eating this food ' was independently associated with full compliance with nut/seed reintroduction advice (aOR 5.6, 95% CI 1.55–20.8, P = 0.009). Conclusion: This study demonstrates that compliance with local guidelines on nut/seed reintroduction is poor. There is a need to ensure that all patients receive optimal support/information on the day of the food challenge. More thorough assessment prior to the challenge of whether patients and their families are suitable for, and committed to selective nut/seed eating, may result in improved compliance.